Towards a better understanding of wetting regimes at the interface asphalt/aggregate during warm-mix process of asphalt mixtures. (15th February 2017) - Vassaux, S.; Gaudefroy, V.; Boulangé, L.; Pévère, A.; Mouillet, V.; Barragan-Montero, V.
Highlights: Asphalt surface tension is related to the aromatic and asphaltenes content. Asphalt viscosity and asphaltenes content impact equilibrium contact angles. Substrate heterogeneities improve wetting quality on mineral surfaces. A complete characterization of mineral substrates by SEM is highly recommended. The CBOW model is a promising approach to characterize substrate heterogeneity. Abstract: In road applications, the current challenge is to develop more ecological products while maintaining asphalt mixture performance and durability. This sustainable development politics in civil engineering leads to promote techniques saving both energy and raw materials like combining the use of warm mix asphalt concretes (WMA) with the use of reclaimed asphalt pavement (RA). However, one of the current problematic when combining WMA and RA is to assess the quality adhesion of the "asphalt/aggregate" couple that is a fundamental parameter for the good mixture properties at short time and thereby durability of this composite structure. Indeed, the reduction of the manufacture temperature and the use of an aged binder may also have consequences on adhesion quality between asphalt and aggregates. It is the reason why it is crucial to identify the most impacting factors of wetting phenomena at the interface "asphalt/aggregate". So, in this paper, the role of asphalt characteristics (viscosity, ageing, composition) as well as the one of substrate was investigated. The substrate heterogeneity degree determines asphalt wetting behavior. For a model glass substrate, only asphalt characteristics have an impact: asphalt viscosity, polarity and saturates content are influent factors. On the mineral heterogeneous substrate, asphalt viscosity and asphaltenes content have an impact on wetting indicators. Substrate heterogeneities also appear as a very important factor which improves considerably wetting quality. The tested mineral substrate has been revealed as a biphasic composite material for which the wetting regime was modeled by a Cassie-Baxter model. A comprehensive approach has been proposed to explain asphalt wetting on heterogeneous substrates in correlation with Scanning Electron Microscopy observations. This Cassie-Baxter model is essential to understand adhesion phenomena on heterogeneous road materials. It seems also to be a promising way to evaluate quality adhesion of "asphalt/RA" mixtures.